Fatigue damage ratios for heavy vehicles operating in the southern part of Malaysian Peninsula - Mahmoud Yassenn O.; Endut I.R.; Hafez M.A.; Ishak S.Z.; Kordi N.E. (Springer Verlag, 2023)
Management science; Pavements; Vehicles; Flexible pavement designs; Flexible pavements; Heavy vehicle; Malaysia; Malaysians; Traffic volumes; Weight in motions; Fatigue damage